Synthesis and characterization of filtered-cathodic-vacuum-arc-deposited TiO2 films for photovoltaic applications - Aramwit C. (2014)
Titanium dioxide (TiO2) is well-known as a photovoltaic and photocatalytic material. For improvement in the dye-sensitized solar cell (DSSC) performance efficiency, the photocatalyst TiO2 layer would be desired in nanoporous anatase. In this research, TiO2 films were synthesized on glass or p-type silicon substrate using our in-house Filtered Cathodic Vacuum Arc Deposition (FCVAD) system. The deposition was operated at varied oxygen (O2) partial pressures of 10-4, 10 -3, 10-2 to 10-1 torr with fixed 0 or 250-V bias and 600-V arc for 10 or 20 minutes. The film transparency increased with increasing of the O2 pressure, indicating increase in the structure required for applications in dye-sensitized solar cells. The films were characterized using the Energy-Dispersive X-ray spectroscopy (EDS) and Raman spectroscopy techniques. The EDS confirmed that the transparent deposited films contained stoichiometric titanium and oxygen under the medium O2 pressure. Raman spectra confirmed that the films were TiO2 containing some rutile but no anatase which needed annealing to form. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) were used for evaluation of the film's surface morphology and thickness. The result showed that increasing of the O2 pressure decreased the thickness to a nanoscale but increased the amount of TiO2. © IOP Publishing Ltd 2013.